SEKULARISME PROSES PENYUSUNAN ANGGARAN BERBASIS PARTISIPATIF DALAM PERSPEKTIF ISLAM - Arief Rahman (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
The purpose of this paper is to explain the mechanism of the budget process are subjected to various distortions that lead to secularization in the budgeting process that impact on the neglect of the interests of society. It will also offer the concept of budgeting from an Islamic perspective. This perspective is used to provide another alternative in compiling the budget that focuses on transparency and participation in the budget in favor of the interests of the community with the Islamic perspective.